Load-bearing capacity of traditional dovetail carpentry joints with and without dowels: comparison of experimental and analytical results - Sobra, Karel (2016)
Post-disaster field studies widely suggest that historical timber structures are seismically resistant, and a growing number of experimental studies support this observation. The joints between structural members, which are the major energy dissipation mechanism within the structure, play a crucial role in the overall robustness and the way that a structure handles the seismic demand. Joints mostly fail when the timber members are still in the elastic range, therefore a thorough understanding of their behaviour under various loading schemes is of utmost importance to gain deeper insight about the overall structural performance of timber structures. This paper summarizes the findings from a series of testing carried out on dovetail joints, which is one of the most common traditional carpentry joints, during the 5th COST FP 1101 Training School, held in University of Minho, Portugal. Within this framework, a dovetail joint (with and without dowel) was tested under compression and tension. The experimentally obtained load-bearing capacity of the joints was then compared to the capacity values calculated using analytical models, and the failure modes were further discussed. The results showed that the experimentally obtained capacity values can be successfully reproduced by analytical models for dovetail joints without dowel. On the other hand, the capacity of a dovetail joint with dowel under compression or tension is always underestimated by analytical models.